2017
DOI: 10.4102/sajid.v32i2.53
|View full text |Cite
|
Sign up to set email alerts
|

Pathological vestibular symptoms presenting in a group of adults with HIV/AIDS in Johannesburg, South Africa

Abstract: Aim: The current study aimed to explore the pathological vestibular symptoms presenting in a group of adults with HIV/AIDS in Johannesburg, South Africa.Design: A quantitative non-experimental research design was adopted where data was collected by means of a questionnaire with close-ended questions on 96 participants who were recruited from a teaching hospital’s HIV/AIDS research unit.Analysis: Data were analysed through descriptive statistics.Results: Findings from the current study revealed that 17% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Evidence linking these HIV treatments to ototoxicity demonstrates that the ototoxic effects create a burden and a distinctive challenge to the provision of ear-and-hearing health care service delivery in South Africa (HPCSA 2018;Hollander, Joubert & Schellack 2020;Khoza-Shangase 2010a; Khoza-Shangase & Masondo 2020; Khoza-Shangase & Prodromos 2021; Khoza-Shangase & Van Rie 2017;. The evidence further supports the development and implementation of systematic and standardised ototoxicity monitoring protocols, such as the ototoxicity grading system within a mobile app for resource-limited settings that are recommended by Hollander et al (2020).…”
Section: Delving Into Ototoxicitymentioning
confidence: 99%
“…Evidence linking these HIV treatments to ototoxicity demonstrates that the ototoxic effects create a burden and a distinctive challenge to the provision of ear-and-hearing health care service delivery in South Africa (HPCSA 2018;Hollander, Joubert & Schellack 2020;Khoza-Shangase 2010a; Khoza-Shangase & Masondo 2020; Khoza-Shangase & Prodromos 2021; Khoza-Shangase & Van Rie 2017;. The evidence further supports the development and implementation of systematic and standardised ototoxicity monitoring protocols, such as the ototoxicity grading system within a mobile app for resource-limited settings that are recommended by Hollander et al (2020).…”
Section: Delving Into Ototoxicitymentioning
confidence: 99%
“…Identificar a presença, a gravidade e a natureza das manifestações vestibulares em pacientes com HIV / AIDS é de vital importância para os profissionais de saúde, pois os sintomas vestibulares podem ser debilitantes e afetar negativamente a qualidade de vida (Shangase 2017;Holmes & Padgham, 2010).…”
Section: Introductionunclassified
“…tenha havido um aumento no número de participantes que relataram vertigem na sessão de avaliação de três meses após o início da HAART, esse número diminuiu para 0% ao longo do tempo em ambos os grupos; o que levantou um índice de suspeita sobre possíveis efeitos colaterais vestibulares precoces no início da HAART.Em concordância com um estudo que incluiu 96 indivíduos avaliados, seis (22%) relataram ter experimentado outros sintomas vestibulares patológicos debilitantes. Os resultados mostram que os sintomas vestibulares patológicos mais comuns foram: vertigem, tontura, desequilíbrio, dores de cabeça, alterações visuais, náuseas e vômitos(Shangase & Rie, 2017). No entanto em uma análise exploratória com pessoas de idade entre 18-65 o rastreamento e a prevenção de quedas podem ser importantes nessa população em idades relativamente jovens, visto que uma grande proporção de PVHIV (idade mediana, <40 anos) relataram quedas anteriores, e demonstraram redução da qualidade óssea(Berner et al, 2019).Acerca disso os dados podem ser comparados com o estudo que conduziu 15 homens idosos afro-americanos sedentários com HIV e sem HIV, através da Escala de Equilíbrio de Berg (BBS) e o Índice de Marcha Dinâmica (DGI),…”
unclassified
“… 7 On the contrary, a study that was conducted in South Africa by showed that SCC was the most prevalent of their lung cancer cases. 8 The most common risk factor for lung cancer is cigarette smoking, but in addition, there are others including genetic factors, age, occupational hazards, radon exposure, radiation therapy and second-hand smoke. 9 …”
Section: Introductionmentioning
confidence: 99%